A resilient foam material

CN120228977BActive Publication Date: 2026-10-23QUANZHOU BAOFENG SHOES CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510606744.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-12
Publication Date
2026-10-23
Estimated Expiration
2045-05-12

AI Technical Summary

Technical Problem

[0005]本发明的目的是为了克服现有技术存在的发泡材料弹性不够大且缓冲效果不够理想的缺陷,提供一种弹性发泡材料,本发明的发泡材料轻质且高弹,有效提升弹性和缓冲性能,利于获得高弹性、高缓冲性能和更轻便的发泡材料,进而能用于高弹鞋底、减震材料等领域,进一步拓宽发泡材料的应用场景

Benefits of technology

本发明通过上述技术方案,尤其是采用特定组成的原料A和原料B配合上述特定的制备方式,能够在至少两层材料C之间的涂覆位置发大泡,从而获得轻质回复性能好、且高弹的发泡材料,有效提升发泡材料的弹性和缓冲性能,同时进一步降低密度,利于获得高弹性、高缓冲性能和更轻便的发泡材料,进而能用于高弹鞋底、减震材料等领域,进一步拓宽发泡材料的应用场景。一种可能的原理猜测是:原料B中包含第一石墨烯和六种溶剂,第一石墨烯作为造孔材料起到防交联和隔离的作用,且由于在硫化过程中所含的有机溶剂挥发,产生高压静态压力,第一石墨烯在瞬间(如10min左右)撑起,第一石墨烯在打开时会黏在材料C壁上起到支持作用,给出更大的弹性,从而使得第一石墨烯充分且均匀的在硫化过程中瞬间发大泡,进而获得高弹性能和优异的回复性能。而在相同条件下,若将原料B中的第一石墨烯直接添加到原料A中引入,会导致无法造孔发泡,弹性差。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120228977B_ABST
    Figure CN120228977B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of foamed materials, and particularly relates to an elastic foamed material, which is obtained by laminating at least two layers of material C, coating raw material B between the at least two layers of material C, and then vulcanizing once, wherein the material C is obtained by mixing and opening raw material A; wherein the raw material A comprises 50%-75% of ethylene-vinyl acetate copolymer, 1%-10% of a foaming agent, and 0.01%-3% of a crosslinking agent; the raw material B comprises 20%-40% of first graphene, 8%-10% of polyethylene glycol, 2%-5% of polyvinylpyrrolidone, 0.5%-1.5% of ethylene glycol, 6%-10% of sodium carboxymethyl cellulose, 3%-5% of ammonia water, and water; the foamed material is light and high in elasticity, effectively improves the elasticity and cushioning performance, is beneficial to obtaining a foamed material high in elasticity, high in cushioning performance, and light in weight, and can be used in the fields of high-elastic shoe soles, shock-absorbing materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of foam materials technology, and specifically relates to an elastic foam material. Background Technology

[0002] Foamed materials, due to their light weight and good flexibility, possess functions such as cushioning, sound absorption, shock absorption, heat insulation, and filtration, and are widely used in the manufacture of sports equipment, cushioning pads, children's flooring, and sports shoes. However, the application of different foamed sole materials presents different challenges. For example, EVA foamed soles lack sufficient mechanical strength, tear resistance, and peel resistance; therefore, the application of foamed materials in shoe soles is somewhat limited. Graphene, with its unique two-dimensional periodic honeycomb lattice structure and the stable six-membered carbon rings in its structural units, endows it with excellent thermal, mechanical, and electrical properties. Therefore, adding graphene to foamed materials can effectively improve the tear resistance, peel resistance, and other mechanical properties of foamed soles, thereby broadening the application range of shoe soles.

[0003] However, existing foamed materials lack sufficient elasticity to meet the requirements of specialized applications such as high-elasticity shoe soles and high-elasticity shock-absorbing materials. Furthermore, when graphene is used in foamed materials, its enormous specific surface area and inherent van der Waals forces between its layers make it prone to agglomeration. Simultaneously, low polarity and poor compatibility with low-polarity copolymers like ethylene-vinyl acetate copolymers make it difficult to peel graphene from these copolymers. Therefore, simply adding graphene to foamed materials does not significantly improve their performance.

[0004] It should be noted that this part of the present invention only provides background technology related to the present invention, and does not necessarily constitute prior art or known technology. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing foam materials, such as insufficient elasticity and unsatisfactory cushioning effect, and to provide an elastic foam material. The foam material of this invention is lightweight and highly elastic, effectively improving elasticity and cushioning performance. It is conducive to obtaining foam materials with high elasticity, high cushioning performance and lighter weight, and can be used in fields such as high-elastic shoe soles and shock-absorbing materials, further expanding the application scenarios of foam materials.

[0006] To achieve the above objectives, the present invention provides an elastic foam material, which is obtained by laminating at least two layers of material C and coating raw material B between the at least two layers of material C, followed by vulcanization. Material C is obtained by mixing and kneading raw material A. Among them, based on the weight percentage of each component contained in raw material A, raw material A contains 50%-75% ethylene-vinyl acetate copolymer, 1%-10% foaming agent, and 0.01%-3% crosslinking agent; Based on the weight percentage of each component in raw material B, raw material B contains 20%-40% first graphene, 8%-10% polyethylene glycol, 2%-5% polyvinylpyrrolidone, 0.5%-1.5% ethylene glycol, 6%-10% sodium carboxymethyl cellulose, 3%-5% ammonia, and water.

[0007] In some preferred embodiments of the present invention, the total coating area of ​​raw material B accounts for 20%-80% of the surface area of ​​material C.

[0008] In some preferred embodiments of the present invention, the distance between adjacent coated raw materials B is 1-50 mm along the X-axis direction of material C; and the distance between adjacent coated raw materials B is 1-50 mm along the Y-axis direction of material C.

[0009] In some preferred embodiments of the present invention, the elastic foam material has micropores at the location where raw material B is coated, and the size of the micropores is 0.1-10 mm.

[0010] In some preferred embodiments of the present invention, the ratio of the coating thickness of raw material B to the thickness of the adjacent material C is 0.001-0.5:1, and / or the coating thickness of raw material B is 1-1200 μm.

[0011] In some preferred embodiments of the present invention, raw material A further comprises 0.5%-23% foaming accelerator and 3%-20% filler, based on the weight percentage of each component contained in raw material A.

[0012] More preferably, the foaming accelerator includes at least one of stearic acid, zinc stearate, and zinc oxide. Based on the weight percentage of the corresponding components contained in raw material A, the content of stearic acid is 0.1%-2% when stearic acid is present, the content of zinc stearate is 0.1%-2% when zinc stearate is present, and the content of zinc oxide is 0.5%-20% when zinc oxide is present.

[0013] More preferably, the filler comprises calcium powder and / or talc.

[0014] More preferably, in raw material A, the crosslinking agent includes dicumyl peroxide and / or azodicarbonamide.

[0015] In some preferred embodiments of the present invention, raw material A further comprises a second graphene, wherein the mass amount of the second graphene is 1%-5% of the total mass of the other components in raw material A besides the second graphene. In some preferred embodiments of the present invention, the process of mixing raw material A includes: mixing ethylene-vinyl acetate copolymer, filler, and second graphene in a first mixing, and then mixing a foaming agent, crosslinking agent, and foaming accelerator in a second mixing; wherein the first mixing time is 3-15 min, the second mixing time is 1-8 min, and the temperatures of the first mixing and the second mixing are each independently between 110℃ and 170℃.

[0016] In some preferred embodiments of the present invention, raw material A further comprises 5%-20% polyolefin elastomer, 3%-15% thermoplastic elastomer, and 0%-2%, more preferably 0.1%-2% additives, based on the weight percentage of raw material A.

[0017] In some preferred embodiments of the present invention, the process of mixing raw material A includes: first mixing ethylene-vinyl acetate copolymer, polyolefin elastomer, thermoplastic elastomer, filler and additives, and then adding foaming agent, crosslinking agent and foaming accelerator for second mixing, wherein the first mixing time is 3-15 min, the second mixing time is 1-8 min, and the temperature of the first mixing and the second mixing are each independently between 110℃ and 160℃.

[0018] In some preferred embodiments of the present invention, the thermoplastic elastomer is selected from at least one of ethylene-methacrylic acid copolymer, styrene-ethylene-butene-styrene copolymer, styrene-butene-styrene copolymer, and thermoplastic polyurethane, and the additive is selected from at least one of flow aid and reactive additive.

[0019] In some preferred embodiments of the present invention, the conditions for initial smelting include: an initial smelting temperature of 80-100℃ and an initial smelting time of 7-10 min; the conditions for primary vulcanization include: a vulcanization temperature of 165℃-185℃ and a vulcanization time of 20-25 min.

[0020] In some preferred embodiments of the present invention, a secondary vulcanization is performed after the initial vulcanization. The conditions for the secondary vulcanization include a temperature of 150-160°C and a time of 5-10 minutes.

[0021] Beneficial effects: This invention, through the aforementioned technical solution, particularly the use of raw materials A and B with specific compositions and the aforementioned specific preparation method, enables the formation of large bubbles at the coating location between at least two layers of material C. This results in a lightweight foamed material with good resilience and high elasticity, effectively improving the elasticity and cushioning performance of the foamed material while further reducing its density. This facilitates the production of highly elastic, highly cushioning, and lighter foamed materials, which can then be used in high-elasticity shoe soles, shock-absorbing materials, and other fields, further expanding the application scenarios of foamed materials. One possible principle is that raw material B contains a first graphene and six solvents. The first graphene acts as a pore-forming material, preventing cross-linking and providing isolation. During vulcanization, the evaporation of organic solvents generates high static pressure, causing the first graphene to expand instantaneously (e.g., within about 10 minutes). When the first graphene expands, it adheres to the wall of material C, providing support and greater elasticity. This allows the first graphene to fully and uniformly form large bubbles instantaneously during vulcanization, resulting in high elasticity and excellent resilience. Under the same conditions, if the first graphene in raw material B is directly added to raw material A, it will result in the inability to form pores and foam, and poor elasticity.

[0022] This invention uses raw material A with a suitable composition to prepare material C, and combines it with raw material B with a suitable composition to obtain a foamed material with central supporting pores, which is beneficial to improve the elasticity of the foamed material while ensuring its cushioning performance.

[0023] Furthermore, research has revealed that graphene, due to its large specific surface area and strong van der Waals forces, is prone to aggregation. A single solvent is typically insufficient to completely overcome the strong interactions between graphene sheets. To address this, this invention employs a combination of solvents. These different components interact with the graphene sheet surface, thereby reducing the attractive forces between sheets and improving its dispersion stability in the solvent. One possible underlying principle is that polyethylene glycol and polyvinylpyrrolidone can form stable shells through physical adsorption or chemical bonding, preventing graphene aggregation; the addition of ammonia provides an alkaline environment, giving the graphene surface a negative charge and generating electrostatic repulsion, preventing the graphene sheets from approaching each other and agglomerating; and the addition of sodium carboxymethyl cellulose provides steric hindrance, further inhibiting sheet aggregation.

[0024] In a preferred embodiment of the present invention, an appropriate amount of second graphene is added to raw material A, which is more conducive to improving the support and elasticity of material C. Attached Figure Description

[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 This is an electron microscope image showing the length measurement of micropores in a high-elasticity shoe sole material according to an embodiment of the present invention.

[0027] Figure 2 for Figure 1 Electron microscope image of the width measurement of the micropore. Detailed Implementation

[0028] In this invention, unless otherwise stated, directional terms such as "up," "down," "left," and "right" are generally understood in conjunction with the accompanying drawings and the directions shown in actual applications.

[0029] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.

[0030] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0031] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. The terms "optional" and "discretionary" mean that they may or may not be included (or may or may not be present).

[0032] The present invention provides an elastic foam material, which is obtained by laminating at least two layers of material C and coating raw material B between the at least two layers of material C, followed by vulcanization. Material C is obtained by mixing and smelting raw material A.

[0033] In the present invention, the process of "layering at least two layers of material C and coating with raw material B between the at least two layers of material C" is not limited in terms of the order of layering and coating. That is, material C can be layered first and then raw material B can be coated, or raw material B can be coated on the surface of at least one layer of material C first and then layered with another part of material C. Multiple layers and multiple coatings can also be alternated, and the specific method can be determined according to actual needs. During the vulcanization process, micropores are formed at the locations where raw material B is coated.

[0034] Raw material A, by weight percentage, comprises 50%-75% ethylene-vinyl acetate copolymer, 1%-10% foaming agent, and 0.01%-3% crosslinking agent. Using a suitable composition of raw material A ensures uniform mixing, guarantees effective foaming, and facilitates the formation of effective support and elasticity.

[0035] Based on the weight percentage of each component in raw material B, raw material B contains 20%-40% graphene, 8%-10% polyethylene glycol, 2%-5% polyvinylpyrrolidone, 0.5%-1.5% ethylene glycol, 6%-10% sodium carboxymethyl cellulose, 3%-5% ammonia, and water. Using a suitable composition of raw material B allows for the instantaneous formation of large bubbles during vulcanization, which facilitates effective support of the graphene, thereby achieving high elasticity and excellent recovery properties.

[0036] In this invention, the larger the coating area of ​​raw material B, the more pores are formed. The coating area of ​​raw material B can be adjusted according to the required pore size for the desired elasticity. In some preferred embodiments of this invention, the total coating area of ​​raw material B accounts for 20%-80%, preferably 25%-80%, of the surface area of ​​material C. This is more conducive to obtaining a sufficient number of appropriately large micropores, thereby obtaining a highly elastic foamed material.

[0037] In some preferred embodiments of the present invention, the distance between adjacent coated raw material Bs is 1-50 mm, preferably 7-50 mm, along the X-axis direction of material C; and the distance between adjacent coated raw material Bs is 1-50 mm, preferably 7-50 mm, along the Y-axis direction of material C. Using appropriate distances to coat the raw material Bs facilitates obtaining the desired distribution of the pore structure.

[0038] In some preferred embodiments of the present invention, the elastic foam material has micropores at the location where the raw material B is coated, and the size of the micropores is 0.1-10 mm. It is understood that these micropores refer to millimeter-scale pores (i.e., macropores) formed by foaming of the elastic foam material at the location where the raw material B is coated, rather than micrometer-scale pores (micropores) inherent in the foam material itself. The size of the micropores is within the range of 0.1-10 mm in any direction. More preferably, the length and width of the micropores are (0.5-5 mm) × (0.5-10 mm). The present invention uses micropores of suitable size, which is more conducive to obtaining a foam material that simultaneously meets the requirements of elasticity and resilience.

[0039] In some preferred embodiments of the present invention, the ratio of the coating thickness of raw material B to the thickness of adjacent material C is 0.001-0.5:1, preferably 0.01-0.30:1, and more preferably 0.01-0.20:1. This preferred ratio facilitates the creation of pores and control of pore size in the porous material, and ensures adhesion between adjacent materials C, thereby further improving the elasticity and cushioning performance of the foamed material, while further reducing density, thus facilitating the acquisition of a foamed material with high elasticity, high cushioning performance, and lighter weight.

[0040] Preferably, the coating thickness of raw material B is 1-1200 μm, more preferably 1-900 μm, and even more preferably 50-500 μm. Using the preferred coating thickness is more conducive to balancing the instantaneous expansion effect during foaming and the support effect of graphene on the pores after foaming.

[0041] In some preferred embodiments of the present invention, based on the weight percentage of each component contained in raw material A, raw material A further contains 0.5%-23% foaming accelerator and 3%-20% filler, with the filler preferably being 5%-20%. This preferred embodiment is more conducive to improving the foaming uniformity and supporting performance of the foamed material.

[0042] More preferably, the foaming accelerator includes at least one of stearic acid, zinc stearate, and zinc oxide.

[0043] More preferably, based on the weight percentage of the corresponding components in raw material A, the content of stearic acid is 0.1%-2% when stearic acid is present, the content of zinc stearate is 0.1%-2% when zinc stearate is present, and the content of zinc oxide is 0.5%-20%, preferably 1%-20%, when zinc oxide is present. This preferred embodiment is more conducive to the uniform distribution and stability of bubbles during the foaming process, ensuring the mechanical properties of the foamed material.

[0044] More preferably, the filler comprises calcium powder and / or talc.

[0045] More preferably, in raw material A, the crosslinking agent includes dicumyl peroxide and / or azodicarbonamide.

[0046] In some preferred embodiments of the present invention, raw material A further includes a second graphene, the mass of which is 1%-5% of the total mass of the other components in raw material A, which is more conducive to improving the support and elasticity of material C.

[0047] In some preferred embodiments of the present invention, the process of internal mixing of raw material A includes: internal mixing of ethylene-vinyl acetate copolymer, filler, and second graphene, followed by internal mixing with foaming agent, crosslinking agent, and foaming accelerator; wherein the initial internal mixing time is 3-15 minutes, the secondary internal mixing time is 1-8 minutes, and the temperatures of the initial and secondary internal mixing are independently between 110℃ and 170℃, preferably between 110℃ and 165℃. This preferred scheme is more conducive to improving the mixing uniformity and foaming stability of the components in the foaming process.

[0048] In this invention, other necessary compounds and additives can be added to raw material A according to its practical application in high-elastic shoe soles, shock-absorbing materials, etc. In some preferred embodiments of this invention, raw material A further contains, by weight percentage, 5%-20% polyolefin elastomer, 3%-15% thermoplastic elastomer, and 0.1%-2% additives. Polyolefin elastomers include, for example, POE.

[0049] More preferably, the thermoplastic elastomer is selected from at least one of ethylene-methacrylic acid copolymer, styrene-ethylene-butene-styrene copolymer (SEBS), styrene-butene-styrene copolymer (SBS), and thermoplastic polyurethane (TPU). More preferably, the thermoplastic elastomer includes ethylene-methacrylic acid copolymer, and the mass content of ethylene-methacrylic acid copolymer is 1%-10% based on the weight percentage contained in raw material A. The addition of a thermoplastic elastomer to raw material A in this invention provides rubber-like elasticity, which can be melted by heating, enhancing the elasticity and resilience of the foamed material while maintaining the softness of the EVA material. Preferably, an ethylene-methacrylic acid copolymer is also added, which is a copolymer containing polar groups and can act as a bridge between polar and non-polar materials, improving material compatibility. This helps to improve the dispersion uniformity of different components in the composite foamed material (such as ethylene-methacrylic acid copolymer and fillers), preventing material separation, and allowing for better bonding with other polar materials (such as fillers or additives), thereby improving the material's adhesion properties. It also provides excellent flexibility and elasticity, enhancing the toughness and impact resistance of the foamed material.

[0050] More preferably, the additive is selected from at least one of flow aids and active additives.

[0051] In some preferred embodiments of the present invention, the process of internal mixing of raw material A includes: performing a first internal mixing of ethylene-vinyl acetate copolymer, polyolefin elastomer, thermoplastic elastomer, filler, and additives, followed by a second internal mixing with foaming agent, crosslinking agent, and foaming accelerator. The first internal mixing time is 3-15 minutes, the second internal mixing time is 1-8 minutes, and the temperatures of the first and second internal mixing are independently between 110°C and 160°C, preferably 110°C-160°C. This preferred embodiment is more conducive to further improving the elastic properties of the foamed material while achieving uniform dispersion and stable foaming.

[0052] In some preferred embodiments of the present invention, the conditions for initial refining include: a refining temperature of 80-100℃ and a refining time of 7-10 min; the conditions for primary vulcanization include: a vulcanization temperature of 165℃-185℃ and a vulcanization time of 20-25 min. This preferred embodiment is more conducive to the uniform formation of bubbles between material C.

[0053] Other steps can be performed according to the desired shape of the foamed material in this invention. In some preferred embodiments of this invention, a secondary vulcanization is performed after the initial vulcanization, with the conditions for the secondary vulcanization including a temperature of 150-160°C and a time of 5-10 minutes. This preferred embodiment is more conducive to forming foamed material application products with a specific shape and microporous structure.

[0054] The following detailed description of embodiments of the present invention is exemplary and only used to explain the present invention, and should not be construed as limiting the present invention. All raw materials in the examples were commercially available, and the same raw material came from the same source.

[0055] Example 1 High-elastic sole: 1. Based on the weight percentage of each component in raw material A for this step, EVA7470M (ethylene-vinyl acetate copolymer, Formosa Plastics EVA) 60.7%, POE (Dow Chemical POE ENGAGE) 8003) 14.5%, 514D (specifically ethylene-methacrylic acid copolymer, purchased from DuPont) 4.88%, SEBS (styrene-ethylene-butene-styrene copolymer, purchased from Shanghai Better Chemical Co., Ltd.) 8.5%, ultrafine talc powder (purchased from Dongguan Jinxin Powder Technology Co., Ltd., model GF-1250) 4.24%, flow aid (purchased from Lanxess Group, model A-28E) 0.7%, put them into a mixer and mix for 10 minutes, then add foaming agent (purchased from Jinjiang Jiaqi Plastics Technology Co., Ltd., model AC-6000H) 4.1%; DCP (odorless crosslinking agent, dicumyl peroxide) 0.12%; light zinc stearate (purchased from Dongguan Haili Holding Group Co., Ltd.) 0.56%; stearic acid 0.3%; zinc oxide (purchased from Dongguan Haili Holding Group Co., Ltd.) 1.4%, and continue mixing for 5 minutes. The mixing temperature is 160℃.

[0056] 2. After internal mixing, the material is taken out and put into a rolling mill for further mixing. The mixing time is 8 minutes and the mixing temperature is 90℃. The material is then cut into sheets of uniform size and thickness with a thickness of 4mm (i.e., material C) by a cutting machine.

[0057] 3. Take some sheets and coat the top and bottom surfaces of one sheet with graphene pore-forming material (i.e., raw material B) at equal intervals. Place two uncoated sheets on top and bottom of the coated sheet respectively (i.e., a total of three layers, with the middle layer coated with raw material B on both sides). Place them together in a vulcanizing mold for one vulcanization at a vulcanization temperature of 175℃ for 22 minutes. Finally, a material with uniform pores in the middle is obtained. The composition of raw material B is as follows: by mass percentage of each component in raw material B, 30% graphene, 8% polyethylene glycol, 3% polyvinylpyrrolidone, 0.5% ethylene glycol, 7% sodium carboxymethyl cellulose, 4% ammonia, and the balance being water. The total coating area of ​​raw material B accounts for 30% of the surface area of ​​material C, and the distance between adjacent coated raw material B in the X and Y axes is 10 mm. The coating thickness of raw material B is 500 μm, and the ratio of the coating thickness of raw material B to the thickness of adjacent material C is 0.125:1.

[0058] Fourth, the obtained material is cut and placed into a shoe sole mold for secondary vulcanization to obtain the desired shoe sole. The secondary vulcanization temperature is 155℃, and the time is 8 minutes.

[0059] Electron micrographs of the shoe sole material are shown below. Figure 1 and Figure 2As shown, micropores are present at the location of the coating material B, with the micropore size being (3-4 mm) long × (1-2 mm) wide. On the same foamed material obtained, the average size of the multiple micropores was found to be 3.5 mm × 1.5 mm, as measured in the same way.

[0060] Example 2 Vibration damping materials: The composition of raw material A is as follows: by weight percentage of each component in raw material A, EVA7470M (specific source as in Example 1): 70.2%; light calcium powder (calcium carbonate, commercially available): 9.4%; foaming agent (purchased from Jiangsu Suopu (Group) Co., Ltd., model DN6): 1.35%; DCP (diisopropylbenzene peroxide, also known as vulcanizing agent DCP): 0.52%; stearic acid 0.73%; zinc oxide 15.2%; and graphene by mass 2.6%.

[0061] Process flow: 1. Put EVA7470M, light calcium powder and graphene into a mixer and mix for 7 minutes. Then add foaming agent (DN6), DCP, stearic acid and 3300g of zinc oxide and continue mixing for 3 minutes. The mixing temperature is 165℃.

[0062] 2. After internal mixing, the material is taken out and put into a rolling mill for further mixing. The mixing time is 8 minutes and the mixing temperature is 90℃. The material is then cut into sheets of uniform size and thickness of 4mm by a cutting machine.

[0063] 3. Take some sheets and coat the top and bottom surfaces of one sheet with graphene pore-forming material (i.e., raw material B, whose composition is the same as raw material B in Example 1) at equal intervals. Place two other uncoated sheets on the top and bottom of the coated sheet respectively (i.e., a total of three layers, with the middle layer coated with raw material B on both sides). Place them together in the mold of a vulcanizing machine for vulcanization at a vulcanization temperature of 175°C and a vulcanization time of 22 minutes. Finally, an EVA damping material with uniform pores in the middle is obtained.

[0064] Example 3 The experiment was conducted in accordance with Example 1, except that the total coating area of ​​raw material B accounted for 20% of the surface area of ​​material C. The same tests were performed, and the resulting elastic foam material exhibited micropores with an average micropore size of 2.5 mm × 1 mm.

[0065] Example 4 The procedure was carried out in accordance with Example 1, except that the distance between adjacent coated raw materials B was adjusted to 5 mm along the X-axis direction of material C and the distance between adjacent coated raw materials B was adjusted to 5 mm along the Y-axis direction of material C.

[0066] Example 5 The procedure was carried out in accordance with Example 1, except that the coating thickness of raw material B was adjusted to 1000 μm, so that the ratio of the coating thickness to the thickness of the adjacent material C was 0.25:1. The same tests were performed, and the resulting elastic foam material exhibited micropores with an average micropore size of approximately 3.5 × 2.5 mm.

[0067] Example 6 The procedure was carried out in accordance with Example 1, except that no polyolefin elastomer (POE) was added to raw material A.

[0068] Example 7 The procedure was carried out in accordance with Example 1, except that no thermoplastic elastomers (i.e., 514D and SEBS) were added to raw material A.

[0069] Example 8 The procedure was carried out in accordance with Example 2, except that graphene was not added to raw material A.

[0070] Comparative Example 1 The procedure was carried out in accordance with Example 1, except that graphene in raw material B was introduced as a component in raw material A, i.e., no graphene was added to raw material B.

[0071] Comparative Example 2 The process was carried out in accordance with Example 1, except that the raw materials were added in a different way. Specifically, raw material A and raw material B were mixed together, and then subjected to internal mixing, open mixing, and vulcanization (each process condition corresponds to that in Example 1).

[0072] Comparative Example 3 The procedure was carried out in accordance with Example 1, except that polyethylene glycol was not added to raw material B.

[0073] Comparative Example 4 The procedure was carried out in accordance with Example 1, except that polyvinylpyrrolidone was not added to raw material B.

[0074] Comparative Example 5 The procedure was carried out in accordance with Example 1, except that no ammonia was added to raw material B.

[0075] Comparative Example 6 The procedure was carried out in accordance with Example 1, except that sodium carboxymethyl cellulose was not added to raw material B.

[0076] Test case The elastic foam materials obtained in the above embodiments and comparative examples were subjected to performance tests, and the results are shown in Table 1. The test standards for each performance index are as follows: 1) Rebound elasticity was tested according to ISO 4462:2017; 2) Density was tested according to SATRA™ 134 standard; 3) Tear resistance was tested according to ISO 34-1:2022; 4) Tensile strength was tested according to SATRA™ 137; 5) Hardness was tested according to SATRA™ 205. In addition, the test method for cushioning performance is as follows: a raw egg is placed 1m above the corresponding target high-elasticity product, and then released to allow the egg to fall vertically onto the surface of the target high-elasticity product. The egg bounces back, and the height from which it bounces back without breaking is recorded. The rebound height of the egg is shown in Table 1.

[0077] Table 1

[0078] The results above show that, compared with the comparative example, the elastic foam material of the present invention has better resilience than the embodiment of the present invention. It can effectively improve the elasticity and cushioning performance of the foam material, while further reducing the density, which is conducive to obtaining a foam material with high elasticity, high cushioning performance and lighter weight, and further broadening the application scenarios of the foam material.

[0079] Furthermore, as can be seen from Examples 1 and 3-7, the preferred foaming material of the present invention is more conducive to obtaining higher elasticity, cushioning performance and tear resistance, and further improves the physical properties of the luminescent foam material.

[0080] Furthermore, as can be seen from Examples 2 and 8, the preferred foaming material scheme of the present invention is more conducive to further reducing the density of the foaming material, making the foaming material lighter.

[0081] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. An elastic foam material, characterized in that, It is obtained by layering at least two layers of material C, coating the space between the at least two layers of material C with raw material B, and then performing a vulcanization. Material C is obtained by mixing and refining raw material A. Among them, based on the weight percentage of each component contained in raw material A, raw material A contains 50%-75% ethylene-vinyl acetate copolymer, 1%-10% foaming agent, and 0.01%-3% crosslinking agent; Based on the weight percentage of each component in raw material B, raw material B contains 20%-40% first graphene, 8%-10% polyethylene glycol, 2%-5% polyvinylpyrrolidone, 0.5%-1.5% ethylene glycol, 6%-10% sodium carboxymethyl cellulose, 3%-5% ammonia, and water.

2. The elastic foam material according to claim 1, characterized in that, The total coating area of ​​raw material B accounts for 20%-80% of the surface area of ​​material C; and / or, Along the X-axis of material C, the distance between adjacent coated raw material B is 1-50 mm; along the Y-axis of material C, the distance between adjacent coated raw material B is 1-50 mm.

3. The elastic foam material according to claim 1, characterized in that, The elastic foam material has micropores at the location where raw material B is coated, and the size of the micropores is 0.1-10 mm.

4. The elastic foam material according to claim 1 or 3, characterized in that, The ratio of the coating thickness of raw material B to the thickness of the adjacent material C is 0.001-0.5:1, and / or the coating thickness of raw material B is 1-1200 μm.

5. The elastic foam material according to claim 1, characterized in that, Based on the weight percentage of each component in raw material A, raw material A also contains 0.5%-23% foaming accelerator and 3%-20% filler; The foaming accelerator includes at least one of stearic acid, zinc stearate, and zinc oxide. Based on the weight percentage of the corresponding components contained in raw material A, the content of stearic acid is 0.1%-2% when stearic acid is present, the content of zinc stearate is 0.1%-2% when zinc stearate is present, and the content of zinc oxide is 0.5%-20% when zinc oxide is present. The filler includes calcium powder and / or talc powder; In raw material A, the crosslinking agent includes dicumyl peroxide and / or azodicarbonamide.

6. The elastic foam material according to claim 5, characterized in that, Raw material A also contains second graphene, and the mass of second graphene is 1%-5% of the total mass of the other components in raw material A besides second graphene.

7. The elastic foam material according to claim 6, characterized in that, The process of mixing raw material A includes: mixing ethylene-vinyl acetate copolymer, filler, and second graphene in a first mixing, and then mixing with foaming agent, crosslinking agent, and foaming accelerator in a second mixing; wherein the first mixing time is 3-15 min, the second mixing time is 1-8 min, and the temperature of the first mixing and the second mixing are independently between 110℃ and 170℃.

8. The elastic foam material according to claim 5, characterized in that, Based on the weight percentage of raw material A, raw material A also contains 5%-20% polyolefin elastomer, 3%-15% thermoplastic elastomer and / or ethylene-methacrylic acid copolymer, and 0%-2% additives; the thermoplastic elastomer is selected from at least one of styrene-ethylene-butene-styrene copolymer, styrene-butene-styrene copolymer, and thermoplastic polyurethane, and the additives are selected from at least one of flow aids and reactive additives.

9. The elastic foam material according to claim 8, characterized in that, The process of internally mixing raw material A includes: first internally mixing ethylene-vinyl acetate copolymer, polyolefin elastomer, thermoplastic elastomer and / or ethylene-methacrylic acid copolymer, filler and additives, and then adding foaming agent, crosslinking agent and foaming accelerator for second internal mixing. The first internal mixing time is 3-15 min, the second internal mixing time is 1-8 min, and the temperature of the first internal mixing and the second internal mixing are independently between 110℃ and 160℃.

10. The elastic foam material according to claim 1, characterized in that, The conditions for starting the refining process include: a refining temperature of 80-100℃ and a refining time of 7-10 minutes; the conditions for the first vulcanization process include: a vulcanization temperature of 165℃-185℃ and a vulcanization time of 20-25 minutes. And / or, a secondary vulcanization is performed after the vulcanization, and the conditions for the secondary vulcanization include: a temperature of 150-160°C and a time of 5-10 min.

Citation Information

Patent Citations

  • Preparation method of heterogeneity foaming shoe sole

    CN107672106A

  • Wear-resistant foaming shoe material and preparation method thereof

    CN113683809A